1976
DOI: 10.1111/j.1423-0410.1976.tb04830.x
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to the Optimal Use of Human Blood

Abstract: The influence of different variables on the yield of factor VIII in cryoprecipitate as prepared in the Central Laboratory of the Netherlands Red Cross Blood Transfusion Service, was studied. The following conclusions may be drawn: (1) In case blood should be stored, the use of the anticoagulant solution acid citrate dextrose (ACD) is preferable to citrate phosphate dextrose (CPD) or trisodium citrate (TSC). (2) The temperature of stored whole blood should not decrease below 8 degrees C because of a spontaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Another contributing factor may be the relatively high pH of the heparin solution itself (6.5), since Vermeer et al (13) have reported that blood collected into anticoagu lants with pH values below 5.8 rapidly loses 10-15% of the Factor VIII activity. The pH of the heparin solution is well above this critical value, while that of CPD, or CPD plus heparin is 5.7.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another contributing factor may be the relatively high pH of the heparin solution itself (6.5), since Vermeer et al (13) have reported that blood collected into anticoagu lants with pH values below 5.8 rapidly loses 10-15% of the Factor VIII activity. The pH of the heparin solution is well above this critical value, while that of CPD, or CPD plus heparin is 5.7.…”
Section: Resultsmentioning
confidence: 99%
“…While the recovery of Factor VIII depends on the original concentration in the plasma (7,13), a value of 55 ±13% of the initial activity appears to be a representative re covery in the cryoprecipitate from CPD plas ma (3). Approximately 20% of the activity is left in the cryosupernatant with the re maining 25% not accounted for.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These apparently conflicting results are to a large extent explained by the bi-phasic decay of VIII:C in anticoagulated whole blood and plasma argued by several authors [11,12], Initial loss of VIII:C activity in anticoagulated whole blood was found to be rapid; the half-life of VIII:C in plasma separated very soon after collection was also short. In contrast, the second phase of decay was associated with a very long half-life.…”
Section: Age Of Starting Plasmamentioning
confidence: 94%